Traditional Softball Games Effective Modified for Improving Nutritional Status and Physical Fitness in Elementary School Children (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2019)
Traditional children’s games at school have the potential to decrease the prevalence of obesity which tends to increase. Modifications and standardization of the game are needed so that the game can be implemented. The research objective is to develop a modified softball game model and test its effectiveness for improving nutritional status and physical fitness level of elementary school students. The development research design was used to produce the modified softball game model. Field trials of 27 elementary school fifth grade students were carried out with a one group before and after intervention design. The effectiveness of the model was assessed by changes in Z score of body mass index and physical fitness level before and after the intervention. The results of this research prove that the modified softball game model is valid and relevant to the physical education review. Application of the modified softball game model also proved effective in improving the nutritional status and physical fitness level of elementary school students. In the context of overcoming the problem of over nutrition in school-age children, it is recommended that schools and related stake holders implement the modified softball game model consistently.